PERILAKU BERBELANJA IBU RUMAH TANGGA DI CENDANA SWALAYAN KELURAHAN LABUH BARU KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Kurniawan, Budi; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Market housewife is a very lucrative market segment, mengingatukuran (market size) and growth (market growth) were fantastic. It is often underestimated by marketers because during the many who think that the mother is simply a mother whose job taking care of her husband and children. Despite the fact that a mother is not only to control the purchase of her children and her husband, but furthermore, it triggers a domino effect, where the mother affects the purchase of other families so that it can be said that the economic role of women is very large. This is due to factors for the change of the demographic, economic, social, and cultural in women that led to the dominance of women stronger in general. The research aimed to determine the characteristics of a homemaker, housewife's behavior and to determine the factors that influence the behavior apasajakah housewives who shop at Sandalwood Spa Village District of New Labuh Umbrella Sekaki Pekanbaru. The theory is used to answer the problem formulation in this study the authors adopted the social exchange theory. The study design used is descriptive integrates mixed method approach is a combination of quantitative and qualitative research. Respondents were taken from a housewife shopping at supermarkets sandalwood which already meet the characteristics strived to achieve the target as many as 50 people and collecting data using questionnaires and observation method. The results showed that the characteristics of the housewives of the most widely shopped at Sandalwood Spa Village District of New Labuh Umbrella Sekaki Pekanbaru are housewives whose age was 31-40 years. Behavior housewife shopping at Sandalwood Spa influenced the social exchange theory as seen from the successful propositions, propositions stimulation, value propositions and proposition rationality. The most dominant factor influencing the behavior of housewives who shop at Sandalwood Spa Village District of New Labuh Umbrella Sekaki Pekanbaru is the personal factor. Keyword: Shopping Behavior, Housewife